2007
DOI: 10.1021/la0635350
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Protein Adsorption Kinetics Derived from Simultaneous Measurement of Mass Loading and Changes in Surface Energy

Abstract: We describe a novel technology based on changes in the resonant frequency of an acoustically actuated surface and use it to measure temporal changes in the surface energy gamma (N m(-1)) of an elastomeric polymer membrane due to the adsorption of macromolecules from aqueous solution. The resonant elastomeric surface-tension (REST) sensor permits simultaneous determination of mass loading kinetics and gamma(t) for a given adsorption process, thereby providing a multivariable data set from which to build and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 59 publications
(105 reference statements)
2
30
0
Order By: Relevance
“…Similar observations were reported by Clark et al, where the degree of reversibility of protein adsorption was found to decrease with increasing contact time [3]. The observed irreversibility of the desorption process has been attributed to interfacial conformational changes with time of the sorbate molecules resulting in strong interactions between the surface and the adsorbate [1].…”
Section: B Reversibility Of Protein Adsorption On Hd Sam Surfacessupporting
confidence: 85%
“…Similar observations were reported by Clark et al, where the degree of reversibility of protein adsorption was found to decrease with increasing contact time [3]. The observed irreversibility of the desorption process has been attributed to interfacial conformational changes with time of the sorbate molecules resulting in strong interactions between the surface and the adsorbate [1].…”
Section: B Reversibility Of Protein Adsorption On Hd Sam Surfacessupporting
confidence: 85%
“…Understanding how protein arrives at, and adsorbs to, biomaterial surfaces is thus one of the most fundamental problems of biomaterials surface science. It is of practical interest therefore, to consider how this work might impact understanding of the fundamentals of biocompatibility.Based on the findings of this and recent work on protein adsorption [22][23][24]38], we conclude that immersion of a hydrophobic surface into a concentrated, multi-component protein solution such as blood [78,79] leads to virtually instantaneous accumulation of protein molecules from the proximal fluid phase (relative to the timescale of the observable acute biological responses to materials; see Appendix A). Given that (i) surface capacity for protein is actually quite small (in the range of 2-3 mg/m 2 or µmoles/m 2 for kDa-size proteins), (ii) the total blood-protein concentration is large (50-60 mg/mL, [78,79]), and that (iii) proteins exhibit surprisingly little difference in adsorption energetics across a broad range of blood protein types (3 decades in molecular weight, see refs.…”
mentioning
confidence: 61%
“…Using a novel resonant elastomeric surface tension (REST) sensor, Clark et al recently measured rapid mass accumulation of hen egg-white lysozyme associated with much more gradual change in surface energy (tension of adsorbed protein) [38]. Clark et al thus capture the essence of observation (i); relatively fast mass adsorption that is not directly coupled to slow change in interfacial tension.…”
Section: Interpretation Of Principal Experimental Observationsmentioning
confidence: 99%
See 2 more Smart Citations